Análise das ações da Natura Cosméticos S.A. para ser uma referência em sustentabilidade - DOMINGOS, Ana Maria Peres; SILVA, Kátia Elaine Tomé da (004, 2020)
A sustentabilidade é um tema que ganha cada dia mais importância diante das perspectivas ambientais em nosso planeta. Este trabalho tem por objetivo verificar quais as ações são utilizadas pela empresa Natura Cosméticos S.A. para ser considerada referência em sustentabilidade, analisando a possibilidade de implantação destas iniciativas em outras empresas.. Este estudo é de caráter descritivo com uma abordagem qualitativa a partir de um estudo de caso em uma empresa de cosméticos onde foi identificado à estrutura organizacional estabelecida pela empresa em questão e pesquisando os resultados obtidos através de pesquisa bibliográfica. Buscou-se evidenciar a importância do uso da sustentabilidade nas organizações, destacando que a sustentabilidade é de grande importância para alcançar o sucesso empresarial, visto que as organizações necessitam de recursos que as auxiliem a tornarem se mais autossustentáveis. Foi possível verificar que as ações utilizadas pela Natura envolvem todos os aspectos do tripé da sustentabilidade, estão descritas neste trabalho e podem ser replicadas por diferentes organizações.

Sustainability is a theme that is gaining more and more importance in the face of environmental perspectives on our planet.This course conclusion paper aims to verify which actions are used by Natura SA to be considered a benchmark in sustainability and to check the possibility of implementing these initiatives in other companies, showing the paths that the company Natura Cosmetics S/A uses to be a benchmark in sustainability, transmitting the importance of sustainability to organizations and society, generating benefits and value for the parties involved. This study is descriptive, with a qualitative approach, from a case study in a cosmetics company, thus identifying the organizational structure used in the company in question and the analysis of the data obtained in the annual report - 2019, carried out by the highlighted company. Based on the results obtained, it appears that the continuous sustainable actions developed by the company Natura SA are important and that such attitudes contribute to the renewal, preservation and conservation of natural resources, which should serve as a reflection and alert not only for the other companies and for the whole society. Which the strategies related to the paths that the company Natura Cosmetics SA uses to be a reference in sustainability can be used as a model to be applied by companies in the search for a competitive differential, because it has made it one of the most sustainable in Brazil, providing fundamentals of what can be done not to aggravate environmental problems, with planning throughout its chain, from the production of its products to the awareness of each employee of the company. As the company also generates shared value, it creates economic value for the organization and society. It was possible to verify that the actions used by Natura involve all aspects of the sustainability tripod, are described in this work and can be replicated by different organizations.
Analysis of the actions of Natura Cosméticos S.A. to be a reference in sustainability
Keywords: Logística reversa; Gestão ambiental; Sustentabilidade; Consumidor; Gestão e Negócios